Accountability no setor público: uma visão sistêmica sobre os portais de transparência e o controle social dos municípios da Região Metropolitana de Belém, Pará - NUNES, Wane da Paixão (Universidade Federal do Pará, 2024)
For social control to work with active collaboration, in order to promote common well-being and guarantee the interests of all, it is necessary to apply strategies and approaches, in addition to encouraging social participation, through the provision of efficient means of consultation public. Therefore, based on precepts of the Theory of Social Systems, this study aims to analyze the quality of information available on the transparency portals of the municipalities in the Metropolitan Region of Belém, state of Pará, in order to contribute to a more active participation of social control. On a methodological level, the analysis was carried out by collecting data on city hall pages, taking into account the Eppler Model and the National Public Transparency Program and the perception of Civil Society Organizations. The data reveals that RMB management units perform regularly in terms of clarity. They achieved good levels of transparency in the evaluation matrix used. However, they demonstrate regular performance in evaluating the quality of information, suggesting that the clarity and accessibility of information need to be improved. When analyzing OSCs data, a gap in effective communication is observed. The difficulty of navigation, the lack of clarity in the data presented and the lack of details compromise the interaction between public management and society, hindering understanding and effective participation. The combination of results suggests that, although there is compliance with formal criteria, the quality and accessibility of information are insufficient to promote effective communication. As a product, an instant digital social feedback tool was created for use on municipal transparency portals.